Exploring the Strategies and Impediments Facing the Development of Community Information Centres for Rural Development in Nigeria - Igwe, Kingsley N. (Communicate: Journal of Library and Information Science, 2024)
Community information centres are expected to be part of the core infrastructure that are found in local communities in Nigeria. However, various literature had shown that these information centres are hardly found in Nigeria. This is a challenge, which the paper addressed. The paper examined the concept of community information centres (CIC) and their benefits, and strategic feasible ways of establishing CIC, especially through state and local governments, community self-help efforts, constituency projects of political representatives, philanthropists in the community, community projects of age groups, community members/town unions in the diaspora, and attraction of non-governmental organizations and friends of the community. The paper also explored the implications of CIC as agents for sustainable rural development, and identified challenges of establishing such centres, with possible solutions. Thus, the paper concludes that government, communities and their leaders have roles to play in factoring CIC into rural development programmes in Nigeria. In addition, CIC are also expected to be part of the priorities of government for people in the rural areas, due to various benefits of such centres to the lives and existence of rural inhabitants. Some suggestions were made on how CIC could be established and managed, so as to contribute in facilitating the satisfaction of rural dwellers’ information needs and unhindered access to government programmes and services.